Microcephaly and hydrocephalus in a sheep fetus infected with Neospora caninum in Southern Brazil-Short communication - Withoeft J.A.* (2022)
© 2022 Akadémiai Kiadó, Budapest.A case of non-communicating hydrocephalus and microcephaly in a sheep fetus infected with Neospora caninum from Lages, Santa Catarina, Brazil, is reported. Macroscopically, there was moderate flattening and narrowing of the skull, and the portion of the cerebral hemispheres was markedly reduced in size, measuring 3.5 × 3.5 × 0.5 cm, with marked diffuse flattening of the brain gyri and dilation of the lateral ventricles. Cerebrospinal fluid samples were positive to N. caninum detection by PCR. Histologically, there was discrete focal lymphoplasmacytic necrotising encephalitis on the floor of the lateral ventricle, discrete multifocal gliosis and discrete multifocal lymphoplasmacytic myositis. Through the molecular detection of N. caninum in the cerebrospinal fluid, it was possible to report what appears to be the first case of non-communicating hydrocephalus and microcephaly in an ovine fetus infected with N. caninum.